Linguagem em situação de trabalho : cenografia e ethos discursivo em campanhas de vestibular de IES no RS - Battisti, Márcio (2014)
This study, which has an interdisciplinary nature, focuses on language in a work situation manifested in the discursive genres commercial and manual of the candidate for the entrance exam and aims to analyze how they constitute the scenography and the discursive ethos of higher education institutions selected for this research. The choice of this theoretical and applied approach is justified by the fact that all discourse is constructed from an expository scene, condition that validates it and defines the status of the enunciator and coenunciator in the situation of the enunciation. It is through the expository scene that we evidence the discursive ethos revealed by the linguistic choices of the enunciator and built in the staging of speech. The guiding theoretical approach is based in declarative-discursive language on labor, with emphasis on scenography and ethos, having as source Maingueneau (2010a, 2010b, 2010c, 2010d). In the ergological perspective, we highlight Schwartz (2010a, 2010b) and other scholars of the subject, as Durrive (2008, 2010) and Trinquet (2010). The methodological procedures used correspond to an exploratory, qualitative and bibliographic research, with analysis of the selected corpus. The research showed, by studying the set scenography, a discursive ethos of excellence in academic education, an ethos of institution prepared to train qualified professionals for the future demands of the labor market